Discordance of Global Estimates by Patients and Their Physicians in Usual Care of Many Rheumatic Diseases: Association With 5 Scores on a Multidimensional Health Assessment Questionnaire (MDHAQ) That Are Not Found on the Health Assessment Questionnaire (HAQ). Issue 6 (June 2014) - Castrejón, Isabel; Yazici, Yusuf; Samuels, Jonathan; Luta, George; Pincus, Theodore
<x xml:space="preserve">Abstract</x> Objective To analyze discordance between global estimates by patients (PATGL) and their physicians (DOCGL) according to demographic and self‐report variables on a Multidimensional Health Assessment Questionnaire (MDHAQ) in patients with many rheumatic diseases seen in usual care. Methods Each patient completed an MDHAQ at each visit, which includes scores for physical function, pain, and PATGL, each found on the traditional Health Assessment Questionnaire (HAQ), and scores for sleep quality, anxiety, depression, self‐report joint count, and fatigue, which are not found on the HAQ. A random visit of 980 patients with any rheumatic diagnosis was analyzed in 3 categories: PATGL=DOCGL (within 2 of 10 units), PATGL>DOCGL (by ≥2 of 10 units), and DOCGL>PATGL (by ≥2 of 10 units), using descriptive statistics and multinomial logistic regression models. Results Patients included 145 with rheumatoid arthritis, 57 with systemic lupus erythematosus, 173 with osteoarthritis, 348 with other inflammatory diseases, and 257 with other noninflammatory diseases. Overall, PATGL=DOCGL in 509 (52%), PATGL>DOCGL in 371 (38%), and DOCGL>PATGL in 100 (10%). PATGL>DOCGL was associated significantly with older age, female sex, low formal education, Hispanic ethnicity, not working, high MDHAQ physical function and pain scores, and high scores for fatigue, poor sleep, anxiety, depression, and self‐report joint count, which are not available on the HAQ. Pain and fatigue were significant in a final multinomial logistic regression; the other variables may raise awareness of discordance to clinicians. Conclusion Global estimates of patients indicated significantly poorer status than estimates of their physicians in 38% of 980 patients with rheumatic conditions, and were associated with demographic and MDHAQ scores, 5 of which are not available on the HAQ.